ANALISIS PERBANDINGAN EFEKTIVITAS METODE KUIS DAN CERAMAH PADA PELAJARAN PENDIDIKAN AGAMA ISLAM PADA MATERI GHIBAH DAN TABAYUN PADA SISWA SISWI KELAS VII SMP NEGERI 2 KARAWANG TIMUR - Dinda Fadhilah Maulani; Fadila Amelia; Hana Fauziyah; Hilda Rizqy Almira Hakim (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The quiz method is one of the learning assessment methods in which students' understanding, knowledge, or skills of the material they teach are measured. Quizzes are usually short question forms and can be presented in various forms, such as multiple choice, true/false, short fill-in-the-blank, and short questions. Purpose of Using the Quiz Method Assess student understanding quickly Provide direct responses to teachers and students Increase participation and enthusiasm for learning, and Prepare students for exams under time pressure. While the lecture method is one of the conventional learning methods in which the teacher delivers material verbally to students or participants without much involvement from both parties. This approach emphasizes the delivery of data directly from the teacher to the student, similar to someone giving a speech or presentation. Characteristics of the Lecture Method, The teacher becomes the main source of information (focuses on the teacher) Students listen more and take notes, Effective for delivering material in a short time and Does not require many tools or facilities.